The effect of perceived value, customer satisfaction, and customer trust on customer retention - Dani, Rahma; Abror (Universitas Negeri Padang, 2024)
This study aims to analyze how the effect of perceived value, customer satisfaction, customer trust on customer retention of tokopedia customers in padang city. This reserach was conducted using quantitative methods. The population this study are customers who have used to Tokopedia site in the last 2 months. The research sample is 150 respondents. This study uses a structural equation model (SEM) test with smart PLS software as a data analysis tool. The results of this study found that: (1) Perceived value has a positive and significant effect on tokopedia’s customer retention (2) Perceived value has a positive and significant effect on tokopedia customer satisfaction (3) Customer satisfaction has a positive and significant effect on tokopedia’s customer retention (4) Customer satisfaction has a positive and significant effet on tokopedia’s customer trust (5) Customer trust has a positive and significant effect on tokopedia’s customer retention.